Analysis of Learning Difficulties in Class V Elementary School Science Material - Gui, Marsella Desriyarini; Akuba, Mohamad (Journal of Education Method and Learning Strategy, 2024)
The aim of this research is to identify problems in studying science material and the factors that contribute to these problems. This type of research is qualitative and uses a descriptive approach, involving the use of interviews, questionnaires and documentation. The results showed that six students experienced difficulties in learning science. Internal factors that influence science learning difficulties include poor health, physical disabilities, poor intelligence, students' low interest in learning, and lack of motivation to learn. External factors that contribute to difficulties in learning science include parents' less effective educational styles, parents' lack of attention to students' learning activities, poor relationships between parents and children, weak discipline, a home atmosphere that interferes with students' concentration while studying, and the negative influence of the media and friends who do not support a learning culture. The research results show that teachers must provide incentives that can increase students' interest in learning and must be able to find learning problems in the classroom. Parents must monitor their child's learning progress both at school and at home.